A novel multimodular methodology to investigate external cervical tooth resorption. (16th April 2015) - Mavridou, A. M.; Pyka, G.; Kerckhofs, G.; Wevers, M.; Bergmans, L.; Gunst, V.; Huybrechts, B.; Schepers, E.; Hauben, E.; Lambrechts, P.
Abstract: Aim: To introduce a multimodular combination of techniques as a novel minimal invasive approach to investigate efficiently and accurately external cervical resorption (ECR). Methodology: One case of a central incisor with extensive external cervical resorption was selected to demonstrate the potential of a comparative novel study methodology. ECR diagnosis was based on clinical inspection, digital radiography and cone‐beam computed tomography (CBCT). After extraction, the tooth was investigated using microfocus computed tomography (micro‐CT), nano‐CT and hard tissue histology. These techniques were compared for their accuracy and applicability to highlight their advantages and disadvantages. Results: Nano‐CT was more effective than micro‐CT and CBCT for detailed ex vivo exploration of ECR. The reparative tissue, pericanalar resorption resistant sheet (PRRS), pulp tissue reactions, resorption channels and their interconnection with the periodontal ligament space were accurately visualized by detailed processing and analysis of the nano‐CT data set with Dataviewer and CTAn software. Nano‐CT analysis provided better insight in the true extent of the resorption, based on quantitative measurements and 3D visualization of the tooth structure. Nano‐CT imaging results were similar to hard tissue histology at the mineralized tissue level. To clarify the dynamic phenomenon of reparative tissue formation and substitution of the resorbed tissues, nano‐CT needed to be associated with hard tissue histology. Conclusion: Nano‐CT is a fast and minimal invasive technique for the ex vivo analysis and understanding of ECR and is complementary with hard tissue histology. A combined approach of clinical and CBCT examination, with nano‐CT and histological mapping measurements, can provide an ideal platform for future ECR imaging and exploration studies.